Survival and movements of head‐started Mojave desert tortoises. Issue 8 (26th September 2019) - Daly, Jacob A.; Buhlmann, Kurt A.; Todd, Brian D.; Moore, Clinton T.; Peaden, J. Mark; Tuberville, Tracey D.
ABSTRACT: Head‐starting is a conservation strategy in which young animals are protected in captivity temporarily before their release into the wild at a larger size, when their survival is presumably increased. The Mojave desert tortoise ( Gopherus agassizii ) is in decline, and head‐starting has been identified as one of several conservation measures to assist in recovery. To evaluate the efficacy of indoor head‐starting, we released and radio‐tracked 68 juvenile tortoises from a 2015 cohort in the Mojave National Preserve, California, USA. We released 20 tortoises at hatching (control) in September 2015, and reared 28 indoors and 20 outdoors in predator‐proof enclosures for 7 months before releasing them in April 2016. We monitored tortoises at least weekly after release until 27 October 2016, and documented survivorship, movement, and surface activity. We estimated survivorship by treatment and evaluated effects of treatment, proximity to a raven ( Corvus corax ) nest (predator) coincidentally established after release, distance moved between monitoring events, surface activity, and release size on individual fate in a generalized linear model. Although indoor head‐start tortoises reached the size of 5–6‐year‐old wild tortoises by release at 7 months of age, survival did not differ significantly among the 3 treatment groups. Combined annual survival was 0.44 (95% CI = 0.34–0.58). Tortoises that were closer to an active raven nest were significantly more likely to die, as were those seen more often outside their burrows and active aboveground. Predicted estimates for short‐term probability of survival approached 1.0 as distance from a raven nest exceeded approximately 1.6 km. Rearing treatment, movement distance, and body size were not significant predictors of fate over the 1‐year monitoring period. Head‐started tortoises released ≥1.6 km from areas of raven activity will likely have higher short‐term survival. Population recovery through head‐starting alone is unlikely to be successful if systemic ecosystem‐level issues, such as habitat degradation and conditions that promote human‐subsidized predators, are not ameliorated. © 2019 The Wildlife Society. Abstract : Indoor head‐started desert tortoises had normal movement and behavior post‐release, but their survival rate was not greater than that of direct‐release or outdoor head‐started tortoises under high predation pressure. Increased risk of raven predation for juvenile tortoises occurs up to 1.6 km from active raven nests, and identifying offending ravens based on presence of tortoise carcasses under perch sites may prove difficult.